Analogous wheat root rhizosphere microbial successions in field and greenhouse trials in the presence of biocontrol agents Paenibacillus peoriae SP9 and Streptomyces fulvissimus FU14. (14th February 2020) - Araujo, Ricardo; Dunlap, Christopher; Franco, Christopher M.M.
Abstract: Two Pythium ‐infested soils were used to compare the wheat root and rhizosphere soil microbial communities from plants grown in the field or in greenhouse trials and their stability in the presence of biocontrol agents. Bacteria showed the highest diversity at early stages of wheat growth in both field and greenhouse trials, while fungal diversity increased later on, at 12 weeks of the crop cycle. The microbial communities were stable in roots and rhizosphere samples across both soil types used in this study. Such stability was also observed irrespective of the cultivation system (field or greenhouse) or addition of biocontrol coatings to wheat seeds to control Pythium disease (in this study soil infected with Pythium sp. clade F was tested). In greenhouse plant roots, Archaeorhizomyces, Debaryomyces, Delftia, and unclassified Pseudeurotiaceae were significantly reduced when compared to plant roots obtained from the field trials. Some operational taxonomic units (OTUs) represented genetic determinants clearly transmitted vertically by seed endophytes (specific OTUs were found in plant roots) and the plant microbiota was enriched over time by OTUs from the rhizosphere soil. This study provided key information regarding the microbial communities associated with wheat roots and rhizosphere soils at different stages of plant growth and the role that Paenibacillus and Streptomyces strains play as biocontrol agents in supporting plant growth in infested soils. Abstract : The microbial communities were stable in wheat roots and rhizosphere soils exposed to Pythium and protected by biocontrol agents, whether the plants were grown in the field or greenhouse trials.